ANALISIS LAPORAN KEUANGAN DAERAH BERDASARKAN PERATURAN PEMERINTAH REPUBLIK INDONESIA NO. 24 TAHUN 2005 TENTANG STANDAR AKUNTANSI PEMERINTAH (SAP) - Nur Hayati (MediaTrend, 2010)
The purpose of this study was to describe the accounting system of local finance in the areas of financial management regarding financial reporting areas that are implemented in Jombang by looking anilis regional financial ratios, and analyze the factors that hinder the preparation and financial reporting areas of financial management of the areas in Jombang is based on PP No. RI 24 tahun 2005 tentang Standart Akuntansi Pemerintah. 24 year 2005 regarding Government Accounting Standart. This research is a descriptive study with case study method, which describes the implementation of the regional financial system in Jombang. Data collected in the form of interviews and data analysis pendukung.Berdasarkan results of the analysis conducted in this study, the general realization of the Budget Report, the Consolidated Balance Sheet, Cash Flow Statement, especially in its function as a regional financial statement presentation and preparation is already in the system in accordance with the provisions of praturan ie PP RI No. 24 of 2005 concerning Government Accounting Standard (SAP), but in the assessment of regional financial ratio analysis can bulum fully meet the expectations and objectives of internal control regions as expected in the current era of regional autonomy. Factors that hinder the implementation of local government financial accounting systems, especially in the preparation and financial reporting area is in terms of quality human resources and infrastructure is not adequate.